Upaya Pemerintah Dalam Mengurangi Dampak Negatif Pertambangan Batu Hitam Di Daerah Gorontalo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Black stone mining is one of the trades carried out in several areas of Gorontalo which have mineral mining potential. Unfortunately, in some areas, mining is often carried out without permits, even though there is good mining potential in that location. To collect and describe information directly, this research uses the right approach. This method involves gathering important information through interviews, studies, and participatory perceptions at exploration locations. Next, the data obtained is examined using measurable techniques to differentiate examples and identify relationships between mining activities and the impacts they have on the environment and society. The police have planned a “Central Conversation” (FGD). The aim of the FGD is to find appropriate and feasible arrangements to resolve this issue collectively.